الاتجاهات الفكرية في نقد المقرا عند علماء اليهود معتنقي الإسلام فيما بين (القرنين 6 - 8 هـ) - دراسة نقدية - عبير الحديدي محمد الصياد (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd)
يُعد تحقيق المخطوطات منهجًا علميًا دقيقًا ومحمودًا للكشف عن مكنونات التراث الإنساني على مر العصور، لإبراز الاتجاهات والمفاهيم الفكرية السائدة في فترات زمنية ومناطق جغرافية عند المفكرين. وقد حظي تحقيق التراث الإسلامي الثري باهتمام كبير من قِبَل المحققين ما أدى إلى الكشف عن مكنوناته في شتى المجالات العلمية والأدبية والدينية المختلفة التي كان من أبرزها ما اهتم منها بعلوم مقارنة الأديان. ومن بين هذا التراث ما يعود لمعتنقي الإسلام من المتفقهين في الدين من علماء اليهود، الذين أدركوا بعد دراسات متعمقة للعقائد والمفاهيم الدينية في مصادر كلتا الديانتين ما ورد من تناقضات وشبهات في بعض نصوص المقرا، وقدموا البراهين على ذلك.     Examining manuscripts is an accurate and praiseworthy scientific approach to uncovering the hidden contents of human heritage throughout the ages, to highlight the intellectual trends and concepts prevalent in thinkers’ time periods and geographical regions. Investigating the rich Islamic heritage has received great attention from investigators, which has led to revealing its hidden contents in various scientific, literary and religious fields, the most prominent of which is the science of comparative religion.     Among this heritage is what belongs to the converts to Islam among the Jewish scholars, who after in-depth studies of the religious beliefs and concepts in the sources of both religions, realized the contradictions and doubts contained in some of the texts of Al-Maqra, and provided proof of that.